Inventory and Distribution of Bryophyte in The Girimanik Natural Forest Area (NFA), Wonogiri - Utomo, Salsabilla Khaerunnissa; Santhyami, Santhyami (Konservasi Hayati, 2026)
This study aims to identify the diversity and analyze the distribution of mosses (Bryophyte) in various types of habitats in the Girimanik Nature Forest Area (NFA). The main issue in this research is the limited data on the identification and distribution of moss along the spring trails in the area. The method used is exploratory research with a descriptive qualitative approach through systematic line sampling, observation, and species identification in the laboratory. The types of habitats observed were pine forests, mixed forests, coffee plantations, and river areas. The results show that 682 individual mosses were found, belonging to 40 species, 22 families, and 29 genera, with the dominant group being leafy mosses (Bryopsida). The distribution of species shows differences in each habitat, with river areas and pine forests having higher diversity compared to coffee plantations and mixed forests. This pattern is supported by the Shannon-Wiener diversity index (H'), which indicates moderate diversity in pine forests (H' = 2.41) and river areas (H' = 2.32), lower diversity in mixed forests (H' = 2.08), and the lowest diversity in coffee plantations (H' = 1.72), while the overall habitat shows a high diversity value (H' = 3.15). These differences are influenced by environmental factors such as humidity, temperature, soil pH, and substrate availability. The conclusion of this study is that the diversity and distribution of mosses are greatly influenced by environmental conditions, with variation in diversity levels across habitats reflecting the role of microenvironmental gradients in shaping bryophyte community structure.